New Materialist Freedom in Chloé Zhao's Nomadland - Randy Laist (Film-Philosophy, 2024)
In Chloé Zhao's 2020 film Nomadland, Fern's commitment to eschewing a geolocalizable “home” uproots her from conventional patterns of domesticity and transforms her into an inhabitant of planet earth as a whole, enabling a new way of thinking about identity, environment, and the nature of human freedom. The kind of freedom that Fern's narrative evokes stands in deliberate contrast to the masculinized, heroic style of freedom that American films have done so much to promulgate. In contrast to this conventional representation of freedom, new materialist criticism has examined the many ways that human agency emerges from within a dense web of interconnections that bind together human beings with one another, with other life forms, with inanimate matter, and with the cosmic expanses of time and space. Nomadland can be understood as a film that picks up the iconography of conventional American cinematic freedom in order to redirect this iconography into a new materialist worldview.